2017
DOI: 10.3390/ijms18051007
|View full text |Cite
|
Sign up to set email alerts
|

Chloramidine/Bisindolylmaleimide-I-Mediated Inhibition of Exosome and Microvesicle Release and Enhanced Efficacy of Cancer Chemotherapy

Abstract: Microvesicle (MV) release from tumour cells influences drug retention, contributing to cancer drug resistance. Strategically regulating MV release may increase drug retention within cancer cells and allow for lower doses of chemotherapeutic drugs. The contribution of exosomes to drug retention still remains unknown. Potential exosome and MV (EMV) biogenesis inhibitors, tested on human prostate cancer (PC3) cells for their capacity to inhibit EMV release, were also tested on PC3 and MCF-7 (breast cancer) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
164
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 46 publications
(64 reference statements)
1
164
0
Order By: Relevance
“…PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019). While studies on PADs in relation to human pathophysiology, including cancer, autoimmune and neurodegenerative diseases (Wang and Wang, 2013;Witalison et al, 2015;Lange et al, 2017;Kosgodage et al, 2017Kosgodage et al, & 2018 and CNS regeneration (Lange et al, 2011 and2014) exist, relatively little phylogenetic research has been carried out on PADs in relation to normal physiology and evolutionary acquired adaptions of the immune system. Recent comparative studies focussing on roles for PADs in teleost fish have identified post-translational deimination in key proteins of innate, adaptive and mucosal immunity (Magnadóttir et al, 2018a, b;Magnadottir et al, 2019a;Magnadóttir et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019). While studies on PADs in relation to human pathophysiology, including cancer, autoimmune and neurodegenerative diseases (Wang and Wang, 2013;Witalison et al, 2015;Lange et al, 2017;Kosgodage et al, 2017Kosgodage et al, & 2018 and CNS regeneration (Lange et al, 2011 and2014) exist, relatively little phylogenetic research has been carried out on PADs in relation to normal physiology and evolutionary acquired adaptions of the immune system. Recent comparative studies focussing on roles for PADs in teleost fish have identified post-translational deimination in key proteins of innate, adaptive and mucosal immunity (Magnadóttir et al, 2018a, b;Magnadottir et al, 2019a;Magnadóttir et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…As PADs have been identified to be a key regulator of extracellular (EV)-release, a mechanism that has been found to be phylogenetically conserved from bacteria to mammals (Kholia et al, 2015;Kosgodage et al, 2017Kosgodage et al, , 2018Gavinho et al, 2019;Kosgodage et al, 2019), the characterisation of EVs in camelids is of further interest. Extracellular vesicles (EVs) are found in most body fluids and participate in cellular communication via transfer of cargo proteins and genetic material (Inal et al, 2013;Colombo et al, 2014;Lange et al, 2017;Turchinovich et al, 2019;Vagner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthering the profound implications of MVs in tumor survival and progression are their roles in drug resistance. MVs have been noted to mediate the efflux of chemotherapeutics, promoting cell survival, and the number of MVs formed upon drug treatment has been shown to correlate with their chemotherapeutic resistance . MVs have also been demonstrated to transfer the drug resistance molecule p‐glycoprotein in ovarian cancer cells, mediating drug‐resistance in previously drug‐sensitive cells …”
Section: Functional Cargoes In Microvesicles Derived From Tumor Cellsmentioning
confidence: 99%
“…EVs have been detected in multiple body fluids including urine, saliva and blood, making them readily available for analysis . Efforts have also been directed at investigating the therapeutic potential of EVs, both by preventing their formation, and as tools to package and deliver disease modulating proteins or drugs, for enhanced uptake by target cells. This could be in the form of harvested vesicles with innate therapeutic properties, vesicles which are harvested from cells which have been altered to enhance the presence of particular cargo, or vesicles which are loaded with cargo artificially, after their isolation from cells .…”
Section: Introductionmentioning
confidence: 99%